Pelaksanaan Restrukturisasi Kredit terhadap Penyelesaian Perjanjian Kredit Perbankan - Lubis, Raihanah Erwina; Budhiawan, Adlin (Universitas Muhammadiyah Ponorogo, 2025)
This study discusses the implementation of credit restructuring in the settlement of banking credit agreements in Indonesia. Credit restructuring is a corrective effort undertaken by banks for debtors experiencing difficulties in fulfilling their obligations, as regulated in the Financial Services Authority Regulation (POJK) No.11/POJK.03/2015 and No.40/POJK.03/2019, as well as Bank Indonesia Regulation No.14/15/PBI/2012. The research employs a descriptive analytical method, which involves detailed explanations of the topics under discussion The research was conducted at a state-owned bank in Indonesia, which is kept confidential to protect the institution’s privacy. The legal materials used consist of primary and secondary legal sources; primary materials include statutory regulations arranged hierarchically and legally binding in society. The results indicate that the implementation of restructuring involves multiple stages, ranging from credit monitoring, feasibility analysis, to the formulation of the restructuring agreement as part of efforts to rescue problematic credit. Restructuring may involve interest rate reductions, term extensions, principal or interest arrears reductions, additional credit facilities, or conversion of credit into equity participation. Findings also reveal that open communication, transparency, and good faith between debtor and creditor are key to successful restructuring. Furthermore, the success of restructuring is measured by smooth installment payments after restructuring, while failure may result in collateral auction. This study is expected to provide both conceptual and practical contributions to the development of banking law and enhance public understanding of rights and obligations in credit restructuring.